Effect of group psychotherapy in light of glasser approach on risky behavior - Hosein Yarahmadi; Zargham Roomiyani; Hasan Noormohammadi (Gonabad University of Medical Sciences, 2019)
Nowadays, it could be reasonably argued that addressing health issue and contributory factors behind it is vitally important. The prevalence of risky behavior among different groups, especially in teenagers, is one of the most serious health threats. This study aims to determine the effect of group psychotherapy in light of glasser approach on risky behavior. The research is semi-experimental design. The research population contains all the patients correctional and rehabilitation center, among which 24 clients were selected and were assigned randomly in two experiment and control groups. The experiment group received group psychotherapy in light of glasser approach, in ten 90-minute sessions per week. The control group did not receive any interventions. Risky behavior self-administered questionnaire was used in order to gather the data. The results indicate a significant difference between control and experiment group after the implementation of the independent variable in risky behaviors. Given this, it could be concluded that if this approach is used on a group or individual level among clients in correctional and rehabilitation center, the frequency of risky behavior among them will be substantially reduced.